Sorption and desorption of 17β-estradiol to natural sediment - Takigami, H (Water science and technology : a journal of the International Association on Water Pollution Research, 2011)
The sorption and desorption of 17β-estradiol (E2) to various natural sediment were investigated. First, the quantitative solvent-water partition indices were measured. Significant differences were found between the n-octanol-water partition coefficient (K(OW)) and the n-hexane-water partition coefficient (K(HW)) of E2. The value of K(HW) (Log K(HW) = 0.07) is lower than those of two to four ring polyaromatic hydrocarbons (PAHs), while the value of K(OW) (Log K(OW) = 3.99) and that of organic matter-water partition coefficient (K(OC)) onto humic acid (Log K(OC) = 4.30) were similar to those of the PAHs. Five natural sediments of various characteristics and origins were selected for sorption and desorption experiments. Linear isotherms were obtained for sorption and desorption. The equilibrium partitioning coefficients of E2 were well-correlated with their values of weight fraction of organic carbon in sediments (f(OC)). Results suggest that E2 is sorbed mainly onto the organic portion of sediments and that its sorption coefficient can be estimated from K(OW) and f(OC), as in the case of non-polar PAHs. However, because of its polarity, the sorption mechanism of E2 onto sediments cannot be explained solely by the hydrophobic interaction